Oxidação aeróbica de alcóois terpênicos naturais catalisada por sais de Paládio (II) - Luciana Alves Parreira (2016)
In the present work, several catalytic processes for the aerobic (i.e. using molecular oxygen as the stoichiometric oxidant) oxidation of bio-renewable natural terpenes available from various essential oils and showing a recognized therapeutic potential have been developed. In all processes, commercial palladium (II) salts were used either as sole catalysts or in the presence of suitable co-catalysts whose functionwas to assist in the regeneration of reduced palladium species during the catalytic cycle. The common advantages of all the processes developed, as compared to the conventional Wacker process in which the PdCl2/CuCl2 combination is used as the catalyst, are low acidity of the reaction medium and the absence of chloride ions. These features allowed to achieve high selectivities in the oxidation of terpenic substrates despite their strong tendency to undergo structural rearrangements and other undesirable chemical transformations in the presence of both Bronsted and Lewis acids. The following catalytic systems have been used: Pd(OAc)2/p-benzoquinone (BQ) inacetic acid solutions with or without Cu(OAc)2; Pd(OAc)2/Cu(OAc)2 or Pd(OAc)2 solo in methanol solutions and PdCl2 solo in dimethylformamide (DMA) solutions. The catalytic systems based on Pd(OAc)2 and BQ were successfully applied to the oxidation of -bisabolol, linalool and nerol. The oxidation of -bisabolol provided threemajor products resulted from the oxidation of sterically encumbered trisubstituted double bonds of the substrate, either endocycic or acyclic or both together. The oxidation of linalool led to the formation of an aunts due to the intramolecular cyclization of the substrate. All the products derived from linalool and nerol arise from the oxidation of theirtrisubstituted double bonds. Using this catalytic system various poly-funcionalized terpenoids, some of them being novel compounds, were obtained with high selectivities. These products have a strong potential to be used as components in cosmetics, pharmaceuticals and perfume products. The regeneration of both Pd and BQ occurs inthe absence of auxiliary co-catalysts under superatmospheric oxygen pressure. Alternatively, the reactions can be performed under atmospheric pressure in the presence of Cu(OAc)2 to catalyze the oxidation of hydroquinone by molecular oxygen, thus ensuring the regeneration of BQ during the catalytic cycle. The Cu(OAc)2/Pd(OAc)2 catalytic system, also chloride-free, was applied to the oxidation of -bisabolol under nonacidic conditions. The reaction proceeds in aqueousmethanol solutions and gives exclusively the products resulting from the interaction of palladium with the acyclic double bond, which is trisubstituted and sterically encumbered. No concomitant oxidation of the endociclic double bond, which is expected to be more reactive in palladium catalyzed transformations, occurs. Two new compounds wereproduced from the interaction of the acyclic double bond of the substrate with palladium: the main product formed due to the participation of methanol as the external nucleophile; and the minor product, a tetrahydrofuran, formed by an intramolecular attack of thetethered hydroxyl group. The compound with the tetrahydrofuran ring is also formed in the Pd/BQ systems. Palladium based catalytic systems not containing co-catalysts, which are more benign environmentally, have been also tested in the oxidation of several natural terpenes; however, the encouraging results were obtained only with -bisabolol. Two novel selective oxidations of -bisabolol by molecular oxygen under mild nonacidic conditions have been developed, in which palladium salts (PdCl2 or Pd(OAc)2) were used as sole catalysts in the absence of co-catalysts or special ligands for the stabilization of reduced palladium species in solutions. The reactions in aqueous methanol ordimethylacetamide solutions resulted in the products, some of them being novel compounds, derived exclusively from the oxidation of the acyclic double bond, with the endocyclic double bond remaining intact.Simple catalytic procedures developed in the present work represent ecologically and economically attractive routes to interesting poly-functionalized compounds starting from renewable biomass-based substrates. These products are hardly accessible by conventional synthetic methods and are potentially useful in fine chemical industry asingredients or synthetic intermediates.